2010
DOI: 10.1089/ars.2010.3290
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical ATP Elevation in Ischemic Penumbra Revealed by Quantitative Imaging Mass Spectrometry

Abstract: Local responses of energy metabolism during brain ischemia are too heterogeneous to decipher redox distribution between anoxic core and adjacent salvageable regions such as penumbra. Imaging mass spectrometry combined by capillary electrophoresis=mass spectrometry providing quantitative metabolomics revealed spatiotemporal changes in adenylates and NADH in a mouse middle-cerebral artery occlusion model. Unlike the core where ATP decreased, the penumbra displayed paradoxical elevation of ATP despite the constra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 102 publications
(143 citation statements)
references
References 36 publications
6
135
1
1
Order By: Relevance
“…To examine energy metabolism of individual cancer cells in metastatic tumors, we used HCT116 cells labeled with a cell-cycle phase-dependent fluorescent marker system Fucci (19). With this system, newly developed matrixassisted laser desorption/ionization imaging mass spectrometry (MALDI-IMS) with high spatial resolution enabled us to reveal spatial distributions and local concentrations of various metabolites in the cancer cells in different cell-cycle phases in vivo (20). Application of metabolomic analyses using capillary electrophoresis/electrospray ionization/mass spectrometry (CE/ESI/MS; refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine energy metabolism of individual cancer cells in metastatic tumors, we used HCT116 cells labeled with a cell-cycle phase-dependent fluorescent marker system Fucci (19). With this system, newly developed matrixassisted laser desorption/ionization imaging mass spectrometry (MALDI-IMS) with high spatial resolution enabled us to reveal spatial distributions and local concentrations of various metabolites in the cancer cells in different cell-cycle phases in vivo (20). Application of metabolomic analyses using capillary electrophoresis/electrospray ionization/mass spectrometry (CE/ESI/MS; refs.…”
Section: Introductionmentioning
confidence: 99%
“…Application of metabolomic analyses using capillary electrophoresis/electrospray ionization/mass spectrometry (CE/ESI/MS; refs. 21,22) allows us to determine fluxes of multiple metabolic pathways during cell-cycle progression in vitro (20,23,24). MALDI-IMS analyses of metastatic tumors have shown that the cancer cells in G 1 phase were more active in glycolysis than those in the other phases.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40] Moreover, small molecules with high-energy organic phosphates, including nucleotides, as well as signal-transduction molecules such as neurotransmitters, are well known to be sensitive to the PM degradation. 25,40) We have approached this problem by rapidly " xing" the state of metabolites as they exist in vivo. For this purpose, we used a head focused-microwave irradiation method (FMW), [41][42][43][44] in which the enzymes responsible for the decomposition of metabolites in the brain are inactivated within 1 s.…”
Section: Sample Preparation Procedures To Prevent Postmortem Degradmentioning
confidence: 99%
“…e in-situ freezing (ISF) method protected endogenous acetylcholine (ACh) from PM degradation resulting in improved IMS sensitivity e ISF method, which does not require any specialized instrument, was also proven to be e ective for preserving labile metabolites from PM degradation. 24,25,46) In contrast to FMW, the ISF procedure halts the PM enzymatic activity by rapid freezing of the brain tissues, while ensuring adequate blood perfusion until the arrival of the freezing front to avoid unnecessary autolysis. is method has been employed for brain imaging of liable energy nucleotides, 24,25,46) as well as the neurotransmitter ACh, 47,48) since earlier studies showed that the molecular turnover of ACh is quite rapid.…”
Section: Animal Welfarementioning
confidence: 99%
“…Among the many kinds of matrices, sinapinic acid (3,5-dimethoxy-4-hydroxycinnamic acid [SA]) is generally used for high-molecular-weight molecules, such as proteins, while α-cyano-4-hydroxycinnamic acid (CHCA) is often used for medium-molecularweight molecules, such as peptides. 2,6-dihydroxyacetophenone (DHA), DHB, or 9-aminoacridine (9-AA) is generally used for low-molecular-weight molecules, such as pharmaceutical compounds, lipids, or metabolites (Hattori et al, 2010;Hayasaka et al, 2009;Khatib-Shahidi et al, 2006;Sugiura et al, 2009;Woods & Jackson, 2006).…”
Section: Choice Of Matrixmentioning
confidence: 99%